Investigation of thermoelectric properties of nanocrystalline copper chalcogenides - Kubenova, M.M.; Kuterbekov, K.A.; Balapanov, M.Kh.; Ishembetov, R.Kh.; Kabdrakhimova, G.D.; Alina, R.A.; Bulatova, D.; Tatay, M.; Yelibayev, O. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
Modern research efforts are aimed at developing fuel cells characterized by high efficiency, low cost and environmental friendliness, which largely depend on the properties of the corresponding catalyst materials ― the most important components of the fuel cell. Catalysts based on metal chalcogenides, predominantly S based, have activity in accelerating the oxygen reduction reaction comparable to the activity of Pt in H2SO4. The work uses the technique of compacting powder materials and obtained volumetric samples. Nanodisperse powder fractions with an average particle size of (50–100) nm were obtained. The values of the thermo-emf coefficient (about 0.08 mV/K) were obtained for the studied alloy with low defects in the cation sublattice of the Сu2S0.5Te0.5 type. It was found that a decrease in grain size leads to a significant decrease in electronic conductivity for all studied samples. The paper presents the results of a study of the thermoelectric properties of the Cu2S0.5Te0.5 triple alloy. For the studied composition, a decrease in thermal conductivity by (25‒30)% and a slight increase in the thermal emf coefficient compared with large–crystal samples were obtained. Low thermal conductivity was found in the range (0.3–1.1) W m-1 K-1 with a conductivity above 1000 ohms-1cm- 1. For the studied sample Cu2S0.5Te0.5 ― thermoelectric efficiency (ZT = 0.25) at 400 °C, which allows us to hope for the possibility of improving the characteristics of samples of this composition to acceptable values for practical thermoelectric devices by selecting the optimal alloying.
Нанокристалды мыс халькогенидтерінің термоэлектрлік қасиеттерін зерттеу
Исследование термоэлектрических свойств нанокристаллических халькогенидов меди
Keywords: thermoelectric materials; copper sulfide; crystal structure; conductivity; diffusion; thermal conductivity; Seebeck coefficient; superionic conductors